Mechanism of the cis-[Pt(1R,2R-DACH)(H2O)2]2+ intrastrand binding to the double-stranded (pGpG)·(CpC) dinucleotide in aqueous solution: a computational DFT study - Chval, Zdeněk; Kabeláč, Martin; Burda, Jaroslav V (Inorganic chemistry, 2013)
A mechanism of the intrastrand 1,2-cross-link formation between the double-stranded pGpG·CpC dinucleotide (ds(pGpG)) and fully aquated oxaliplatin cis-[Pt(DACH)(H2O)2](2+) (DACH = cyclohexane-1R,2R-diamine) is presented. All structures of the reaction pathways including the transition states (TSs) were fully optimized in water solvent using DFT methodology with dispersion corrections. Both 5' → 3' and 3' → 5' binding directions were considered. In the first step there is a slight kinetic preference for 5'-guanine (5'G) monoadduct formation with an activation Gibbs free energy of 18.7 kcal/mol since the N7 center of the 5'G base is fully exposed to the solvent. On the other hand, the N7 atom of 3'-guanine (3'G) is sterically shielded by 5'G. The lowest energy path for formation of the 3'G monoadduct with an activation barrier of 19.3 kcal/mol is connected with a disruption of the 'DNA-like' structure of ds(pGpG). Monoadduct formation is the rate-determining process. The second step, chelate formation, is kinetically preferred in the 3' → 5' direction. The whole process of the platination is exergonic by up to -18.8 kcal/mol. Structural changes of ds(pGpG), charge transfer effects, and the influence of platination on the G·C base pair interaction strengths are also discussed in detail.
Keywords: nukleotidy; molekulární struktura; molekulární modely; roztoky; voda; Molecular Structure; platina; Models, Molecular; Binding Sites; Quantum Theory; kvantová teorie; Nucleotides; Platinum; Solutions; vazebná místa; Water